‘A perfect Example of the Strong Ion Difference: Hyperchloraemic Acidosis due to 0.9% Normal Saline Irrigation, in a Patient with a Ruptured Bladder’ - Andrew Lane; William Dey (Journal of Clinical Case Reports and Images, 2019)
An 81-year-old male presented to the Emergency Department with urinary retention, subsequent to passing blood clots. A three-way catheter was inserted for continuous bladder irrigation. 48 hours later he deteriorated, with worsening tachypnea and hypoxaemia. Clinical examination and chest x-ray suggested pulmonary odema, managed with intravenous furosemide, and non-invasive ventilation. His irrigation circuit-chart showed he had received 10 litres Normal Saline via the afferent limb, but only 3 litres recorded at the efferent limb. It was suspected the catheter was adjacent to a vascular-cystic interface, however an urgent contrast CT revealed the irrigating catheter perforating the bladder, being situated in the abdominal cavity (see 3 images). His arterial blood-gas analysis demonstrated the expected normal anion-gap academia, however his Strong Ion Difference calculations, sodium-chloride difference of 13 and a normal albumin level, perfectly demonstrated the expected calculated BE of -13. The catheter was withdrawn, and the patient made a full recovery.
Keywords: Strong Ion Difference